Emociones Emergentes en La Historia Personal de Un Grupo De Madres Sustitutas Frente a su Proyecto de Vida (2024)
The purpose of this research is to understand the influence of emerging emotions regarding their life project, in the personal history of a group of substitute mother located in the municipality of Cartago Valle del Cauca, through a qualitative approach, using the focus group technique with narratives, semi-structured interviews, where the emotions that emerge throughout their experience and how these intervene in the decisions related to their life project are explored.